Efektivitas Pembelajaran Secara Daring Kaitannya Dengan Motivasi Belajar Siswa SMAN 1 Tanjunganom - I Ketut Mahardika; Siti Nur Bahiroh; Ayu Putri Wulandari; Thoriq Wildan; Nadya Arini Atmaja; Rizka Elan Fadilah; Firdha Yumar (Jurnal Ilmiah Wahana Pendidikan, 2022)
Along with the times, the development of Information Technology (IT) is also growing rapidly. The need for IT-based teaching and learning concepts and mechanisms is inevitable. When the Covid-19 pandemic hit, information technology was inevitably forced to move forward to meet the needs in the world of education. The concept which was later known as e-learning brought the influence of the transformation process of conventional education into digital form, both content and system. In the research that has been carried out, it is expected to be able to determine the level of motivation in online or distance learning in students majoring in Mathematics and Natural Sciences. This research is a quantitative descriptive study with a total sample of 9 students. Data collection techniques by distributing online questionnaires. The results of the study showed that 66.67% of students were unmotivated to learn online and 33.33% were motivated by online learning. So it can be said that learning is less able to motivate students.